Naive Bayes Classification of Bullying and Non-Bullying Comments in Instagram Social Media Posts - Naflah Faulina (Universitas Muhammadiyah Metro, 2024)
Machine learning is a type of artificial intelligence that provides computers with the ability to learn from data. There are three main branches of machine learning, namely supervised machine learning, unsupervised learning, and reinforcement learning. One of the categories in supervised machine learning is classification. Classification is the process of assessing a data object where the object is put into a certain class from the number of classes available. An example of a classification algorithm is Naive Bayes with classification using probability and statistical methods. This algorithm is used to classify Bullying and Non-bullying with a division of training data and testing data, namely 60:40, 70:30, and 80:20 resulting in the best accuracy value for training data and testing data 60:40 of 66%.